Pengembangan Alat Penilaian Praktikum Fisika di Laboratorium Virtual dengan Bantuan Simulasi PhET - Zhain Zainuddin; A. Kadir; Halmuniati Halmuniati; L.O Asmin; L. Isa; Burhan Burhan; Rani Rani (Pendidikan Fisika UIN Alauddin Makassar, 2024)
This research aims to produce a physics practicum assessment product in a virtual laboratory assisted by PhET Simulation. This study uses research and development with a 4D development model initiated by Thiagarajan & Semmel. The trial participants were 30 students of the IAIN Kendari Physics Study Program, the instrument consisted of interview guidelines, observation sheets and the main instrument was a performance test validated by expert assessments consisting of Assessment Experts, Education Practitioners, Material Experts, and Colleagues. Data analysis and product development trials consisted of qualitative analysis and quantitative analysis. The results of this study indicate that the Physics practicum assessment tool in a virtual laboratory assisted by PhET Simulation developed based on the trial results was declared to meet the aspects of validity, good reliability and was suitable for use.